EXPRESSION OF NEGATIVE TRANSCRIPTION REGULATORS IN PERIPHERAL BLOOD MONONUCLEARS IN PATIENTS WITH BRONCHIAL ASTHMA - V. V. Lim; V. A. Ivanov; L. N. Sorokina; V. N. Mineev; M. A. Nyoma; V. I. Trofimov (Медицинская иммунология, 2016)
Sixty patients with allergic bronchial asthma (ABA) and forty-one, with non-allergic bronchial asthma (NABA), as well as 23 healthy controls were under study. Expression of the SOCS5 mRNA from mononuclear blood cells was analyzed by RT-PCR. In patients with bronchial asthma, (ABA and NABA) we determined a significant increase of mRNA expression levels for a SOCS5 negative transcription regulator in peripheral blood mononuclears, in comparison with control group. Thus, an increase of SOCS5-expression, and of the SOCS3 mRNA expression in patients with BA may be associated with protective anti-inflammatory response.